Assessment of ECG Criteria for the Diagnosis of Right Ventricular Involvement - Suhaib Al-Mashari; Reem Al-Habsi; Amal Al-Habsi; Yasir Al-Malki; Mashaal Al-Saadi; Adil Al-Riyami; Sunil K. Nadar (Oman Medical Journal)
Objectives: This study was performed to assess the accuracy of standard electrocardiographic criteria in diagnosing of right ventricular (RV) involvement in patients with inferior myocardial infarction (IMI). Methods: This was a retrospective analysis of patients admitted with an IMI. Proximal occlusion of the right coronary artery before the origin of the RV branch on angiography was considered diagnostic of RV involvement. Results: The subjects were 129 patients (mean age = 55.8±13.1 years; 81.4% male) with inferior ST-elevation myocardial infarction. The most sensitive indicators of RV involvement were an ST elevation in V4R (72.9%) and a higher ST elevation in lead III than in lead II (80.4%). The most specific indicators were ST elevation in V1 (88.7%) and ST elevation in V1 with ST depression in V2 (97.1%). Combining all the criteria improved sensitivity to 85.7% but reduced specificity to 21.2%. Conclusions: No single electrocardiogram criterion was able to identify all cases of RV involvement in patients with IMI. Combining the different criteria helped pick up more cases at the cost of increasing false positives.